In Vitro Evaluation of a Novel Osteo-Inductive Scaffold for Osteogenic Differentiation of Bone-Marrow Mesenchymal Stem Cells. Issue 2 (March 2020) - Chen, Shuo; Yi, Bao; Su, Liang-bo; Zhang, Yue-Rong; Chen, Chang-Li
Abstract : Background: Demineralized bone matrices (DBMs) were demonstrated to be a promising candidate for bone regeneration by previous studies. However, the limited osteoinductivity of DBMs was insufficient for a better repairing of bone defect. Osteoblasts (OBs), the major cellular component of bone tissues, play an important role in the formation of new bone. The extracellular matrix (ECM) of OB is one of the main components of bone formation niche. Objective: To combine the DBMs with the ECM of OBs to construct a novel scaffold that could be used for bone reconstruction. Methods: In this study, OBs were cultured on the surface of DBMs for 10 days and removed by Triton X-100 and ammonium hydroxide to prepare the OBs-ECM-DBMs (OEDBMs). A series of material features such as residues of OBs and ECM, cytotoxity, and osteoinductive capability of OEDBMs were evaluated. Results: Low cell residues and low content of DNA were observed in OEDBMs. Compared with DBMs, OEDBMs possessed more bone tissues organic matrix proteins, such as osteocalcin, osteopontin, and collagen I. Rat bone marrow mesenchymal stem cells (rBMSCs) presented a good viability when cultured on both 2 materials. The significant upregulations of osteogenic genes and proteins of rBMSCs were observed in OEDBMs group compared with DBMs group. Conclusion: Taken together, these findings suggested that the OB-secreted ECM may be qualified as an ideal modification method for enhancing the performance of engineered bone scaffold. Abstract : Supplemental Digital Content is available in the text